Permasalahan Perempuan Subaltern dalalm Novel Cantik Itu Luka Karya Eka Kurniawan Tinjauan: Poskolonial - Fatonah, Suryani Dwi; Zulfitriyani, Zulfitriyani; Septia, Emil (Universitas Lampung, 2025)
This study analyzes the subaltern aspect according to Gayatri Spivak's theory presented in the novel Cantik itu Luka by Eka Kurniawan. The subaltern theory is motivated by the problem of colonizers who oppress colonized peoples, and in Spivak theory women are often oppressed by colonizers. The purpose of this study is to describe how the problems of subaltern women are told in the novel Cantik itu Luka by Eka Kurniawan, and to describe the form of resistance efforts of subaltern women in the novel Cantik itu Luka by Eka Kurniawan. The data obtained from the novel Cantik itu Luka by Eka Kurniawan was then analyzed using a qualitative method. As a result of this study, there are forms of marginalization, economic impoverishment, stererotype or labeling of women and forms of harassment (sexual harassment and rape). Nevertheless, subaltern women also resist oppressive groups.As for the subaltern women's resistance, namely, open resistance and closed resistance.Keywords: women, subaltern, Spivak, postcolonial, novel